ANALYSIS OF FOREARMS PASSING BASIC MOVEMENTS IN VOLLEYBALL BY USING RESISTANCE BAND TOOLS - Rafika, Rafika; Nur, Suaib; Sari, Puspa (JURNAL PENDIDIKAN GLASSER, 2023)
Passing down is very important to earn points, passing movement is done when receiving services and smashes from the enemy, passing that is not effective can result in defeat the team team. The purpose of this research is to improve the basic movement of passing under the volleyball game. This study used a quantitative method experimentally with a one-group pre test and post test design. In conclusion, the average results of the analysis of the downward passing motion using the resistance band tools, the pretest results get an average value of 16.75 and the posttest results get an average value of 26.33. The average value of the posttest is higher than the average value of the pretest, meaning that there is a contribution by the resistance band tool to the basic movement of passing down